Patient experiences of initial trauma care. (January 2019) - Granström, Anna; Strömmer, Lovisa; Falk, Ann-Charlotte; Schandl, Anna
Highlights: Patients felt safe in a frightening situation. Trauma team members were mostly perceived as professional, well-organised and efficient. Patients were suffering from pain. Patients felt excluded from the dialogue and abandoned when they abruptly were left alone. Abstract: Background: Correct initial treatment of trauma patients reduces mortality and morbidity. However, the initial examination may be perceived as traumatic because of the stressful situation, the unfamiliar setting and the shock of being seriously injured. To date, little is known about patient's experiences of initial trauma management. The aim of this study was to explore trauma patients' experiences of being exposed to initial full trauma team assessment at a Level 1 trauma centre. Methods: Interviews with 16 patients who had been exposed to initial trauma care were conducted at a Level 1 trauma centre, at a Swedish University Hospital. The interviews were transcribed verbatim and analysed with qualitative content analysis. Results: Patients' experiences of initial trauma care can be summarized as: feeling safe in a frightening situation. The trauma team members were mostly perceived as professional, well-organised, and efficient. Yet, the patients described an emotional response to the trauma, physical discomfort during the examination, and feeling prioritised or being ignored in the encounter with the trauma team members. Conclusion: The initial trauma care may be improved if the trauma team members keep the patient's physical and emotional wellbeing in focus and maintain an informative dialogue with the patient during the whole process.